Menghadang Abrasi: Kontribusi Hutan Mangrove Bagi Perlindungan Pesisir Paluh Kurau - Fadilah, Ika Anggi; Simbolon, Krisna Natalin; Manik, Lolona; Tarigan, Sri Winensi; Harefa, Meilinda Suriani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the contribution of mangrove forests to coastal protection in Paluh Kurau, North Sumatra, which is experiencing severe abrasion. Mangrove forests in this area play an important role in dampening waves and maintaining soil stability. However, mangrove forests in Paluh Kurau face serious threats such as land conversion, lack of community participation, and dependence on the government for rehabilitation. As a result, there has been a decrease in the area of mangrove forests and an increase in coastal abrasion. Efforts to conserve and rehabilitate mangrove forests have been carried out by the community and government through mangrove planting and seeding. This study uses a qualitative descriptive method to analyze the condition of abrasion, the role of mangroves, and conservation efforts in Paluh Kurau. The results show the importance of active community involvement and government support in maintaining the sustainability of mangrove forests to protect coastal areas from abrasion.